(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article considers the performing arts, particularly theatre, as practices of feeling that do not limit themselves to offering an affective experience produced by scenic/theatrical effects but instead have the function of potentiating the insight of how and why one feels what one feels. Approaching two recent productions (“Quis saber quem sou”, by Portuguese director Pedro Penim and “Feijoada”, by Brazilian choreographer Calixto Neto), the text sketches out the concept of affective literacy as a way of recognizing and understanding that what one feels results from a social and cultural configuration of affects, which is historically situated. Affective literacy aims at an ethical empowerment of our choices and actions.